The Influence of Perceived Ease of Use of Features on User Satisfaction of the KAI Access Application for Overseas Students in Semarang - Dimas Wahyu Pratama; Eva Miftakhul Janah; Fitriana Zamrotul Ulya; Zulfa Fahmy; Khairani Zikrinawati (LPPM Institut Studi Islam Sunan Doe, 2024)
This research was made to see how the perceptions of overseas students as users of the KAI Access application regarding the ease of use of the KAI Access application features. This study aims to determine the effect of perceived ease of use of features on user satisfaction of the KAI Access application for overseas students in Semarang. The method in this research is a quantitative research method with descriptive analysis. The selected population is overseas students who use the KAI Access application in Semarang. The selected sampling technique is purposive sampling with a sample of 105. Data was collected using the google form to be distributed to overseas students in Semarang who used the KAI Access application. The data analysis technique uses multiple linearity tests with the help of SPSS software. The results of this study prove that perceived ease of use of features has a significant influence on user satisfaction of the KAI Access application for overseas students in Semarang.